Profil Demografik dan Temuan Histomorfologik Karsinoma Payudara di Departemen Patologi Anatomik FKUI/RSCM Periode 2016-2019 Tinjauan Khusus pada Temuan Mitosis Atipik - Juwitasari Wongkar, Fresia; Hellyanti, Tantri; Hayati, Amal (Majalah Patologi Indonesia, 2022)
BackgroundInvasive breast carcinoma (IBC) is the most commonly diagnosed cancer in woman in the world and Indonesia. IBC is classified into two main categories: IBC of no special type (NST) and special types. This retrospective study aims to provide histomorphological profile of mastectomy cases of IBC in Anatomical Pathology Department, Faculty of Medicine, Universitas Indonesia, Dr. Cipto Mangunkusumo General Hospital (PA FKUI/RSCM) 2016-2019.MethodsThis is a descriptive research with cross-sectional design of mastectomy cases, using secondary data from the archives of PA FKUI/RSCM, starting from 2016- 2019. Collecting clinical data as well as observing several histopathologic parameters including histological type, grade, atypical mitotic features, lymphovascular invasion, and lymph node metastases. Tumour classification was made based on the WHO breast criteria in 2019.ResultsDuring the 2016-2019 period there were 144 cases of IBC. 99.3% of cases occurred in female patients, mostly in the age group from 40 to 59 years and unilateral. The majority had tumour sizes ranging >2-5 cm and were stage II. About a third of cases had received neoadjuvant chemotherapy, most commonly in advanced local stage tumors. Most histologic type (65.3%) were IBC of NST and 52.8% of cases were grade 2. There were 92 (63.4%) cases with atypical mitotic features, most commonly found in stage III. Lymphovascular invasion was found in 38.9% of cases and lymph node metastasis was found in 63.2% of cases.ConclusionIBC is the most common cancer in woman, with the most common histologic type were IBC, grade 2, stage II or more. Most of the cases show atypical mitosis, which is most commonly found in stage III. The findings of lymphovascular invasion did not always coincide with the findings of lymph node metastases.